2021
DOI: 10.1073/pnas.1921252118
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding VEGFR1 variants as long-acting VEGF inhibitors for treatment of intraocular neovascular disorders

Abstract: Neovascularization is a key feature of ischemic retinal diseases and the wet form of age-related macular degeneration (AMD), all leading causes of severe vision loss. Vascular endothelial growth factor (VEGF) inhibitors have transformed the treatment of these disorders. Millions of patients have been treated with these drugs worldwide. However, in real-life clinical settings, many patients do not experience the same degree of benefit observed in clinical trials, in part because they receive fewer anti-VEGF inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Pyrogen‐free reagents were employed. To inactivate endotoxin, columns and equipment (Akta Explorer System, GE Healthcare) were sanitized prior to use by exposure to 0.5 N NaOH for approximately 40 min, as described (Xin et al , 2021). LPS levels were measured by ToxinSensor™ Chromogenic LAL Endotoxin Assay Kit (GenScript, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Pyrogen‐free reagents were employed. To inactivate endotoxin, columns and equipment (Akta Explorer System, GE Healthcare) were sanitized prior to use by exposure to 0.5 N NaOH for approximately 40 min, as described (Xin et al , 2021). LPS levels were measured by ToxinSensor™ Chromogenic LAL Endotoxin Assay Kit (GenScript, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…The next series of experiments were performed to investigate the effects of known therapeutic agents on vascular tortuosity in OIR mice using another previously published dataset. (11) Previous reports have demonstrated that intravitreal injections of aflibercept decrease neovascularization and retinal inflammation in OIR mice, but the effects of aflibercept on vascular tortuosity remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The second dataset was previously published by Xin et al and consisted of pooled flat-mount retinal images from OIR mice intravitreally injected with aflibercept versus IgG contralaterally as control. (11)…”
Section: Animalsmentioning
confidence: 99%
“…Biodegradation of hydrogels with chemical polymerization is dependent not only on the nature of the biopolymer but also on stability of crosslinking bonds. For instance, the biodegradable hydrogels were obtained by use of MMP-specific peptide linkers and it was shown that degradation of these hydrogels is matched with cell growth and spreading in culture [ 43 ]. Flexible degradation kinetics mediates an application of hydrogels as delivery vehicles for drugs or as biological active substances.…”
Section: Types Of Wound Dressings (Wds)mentioning
confidence: 99%